Effect of Retention Management on Organizational Commitment with Employee Satisfaction as a Mediation Variable - Pudjiono, Bjardianto; Sihombing, Pardomuan Robinson (Universitas Negeri Malang, 2021)
This study aims to analyze the factors that affect Employee Organizational Commitment at the Human Resources Development Training Center-BPPK Ministry of Finance. The method used in this research is quantitative method with data analysis methods including validity test, reliability test and SmartPLS analysis. While the data collection method in this study used a questionnaire involving all staff of the PSDM-BPPK Ministry of Finance Education and Training. The results of this study prove that retention management has not had a significant direct effect on employee organizational commitment, but has a significant effect on organizational commitment and employee satisfaction as a mediating / intervening variable. Employee satisfaction itself has a direct and significant effect on employee organizational commitment.